2017
DOI: 10.18103/mra.v5i7.1417
|View full text |Cite
|
Sign up to set email alerts
|

What Health Care Providers Know and How They Communicate Breast Cancer Risk to Patients

Abstract: Racial disparities in breast cancer mortality continue, partly due to higher prevalence of an aggressive breast cancer subtype called basallike breast cancer (BBC) in African-Americans. Health care providers (HCPs) are uniquely positioned to discuss cancer risk and prevention with patients. We investigated breast cancer knowledge and risk communication among HCPs to identify factors that influenced communication with patients. Interviews were conducted with 34 HCPs in North Carolina. We found limited evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…43 Previous studies have found that while healthcare providers spend time with women discussing mammography screening recommendations, they tend to spend less time discussing the woman's risk and modifiable risk behaviors. 44,45 Perceived Benefits Interestingly, we found that the participants perceived mammograms as very beneficial. Majority, (80%) of the women, believed that 'if breast cancer is found early, it's likely that the cancer can be successfully treated' and 90% indicated that 'having a mammogram could help find breast cancer when it is first getting started.'…”
Section: Discussionmentioning
confidence: 82%
“…43 Previous studies have found that while healthcare providers spend time with women discussing mammography screening recommendations, they tend to spend less time discussing the woman's risk and modifiable risk behaviors. 44,45 Perceived Benefits Interestingly, we found that the participants perceived mammograms as very beneficial. Majority, (80%) of the women, believed that 'if breast cancer is found early, it's likely that the cancer can be successfully treated' and 90% indicated that 'having a mammogram could help find breast cancer when it is first getting started.'…”
Section: Discussionmentioning
confidence: 82%